Phenotypic and Functional Characterization of Double Negative B Cells in the Blood of Individuals With Obesity - Frasca, Daniela; Diaz, Alain; Romero, Maria; Blomberg, Bonnie B. (Frontiers in Immunology, 2021)
We have previously shown that obesity is associated with increased secretion of IgG antibodies with anti-self reactivity. In this paper, we confirm and extend our previous findings. We show that the plasma of individuals with obesity is enriched in autoimmune antibodies whose levels are positively associated with blood frequencies of the subset of Double Negative (DN) B cells, which is the most pro-inflammatory B cell subset. We also show that DN B cells, significantly increased in the blood of obese versus lean individuals, are characterized by higher expression of immune activation markers and of the transcription factor T-bet, both associated with autoimmunity. The removal of DN B cells from the total B cell pool significantly decreases in vitro secretion of anti-self IgG antibodies. These results altogether confirm the crucial role of DN B cells in the secretion of anti-self IgG antibodies in individuals with obesity.